A new biaxial apparatus for tensile tests on Poly Ethylene Terephthalate optimized specimen at stretch blow molding conditions. (September 2022) - Luo, Yun-Mei; Nguyen, Thanh Tung; Attar, Hanane; Chevalier, Luc; Lesueur, François
Abstract: Characterization of polymer behavior over or near the glass transition temperature in condition close to industrial process remains a scientific goal. In particular being able to manage multiaxial loading at high strain rate and large strains is particularly interesting to understand Poly Ethylene Terephthalate (PET for short) behavior at condition near to the blowing process. In this paper, we present a new vertical biaxial tensile machine that has been designed and built up in our laboratory. In particular, (i) thermal regulation enables a fast and homogeneous heating of the specimen at temperature close to T g, (ii) strain rate up to 5s −1 can be reached and (iii) a cruciform specimen geometry has been optimized to ensure large biaxial strain up to 2 or more in each direction. These two last are lower but close to the strain rate and elongation observed in stretch blow molding. The digital image correlation technique is used to obtain the displacement field and a thermal camera gives the evolution of the temperature field during the test. Dimension and height enables this apparatus to be transportable for mechanical tests under SAXS or WAXS. Here we present results of tests managed on PET and the identification procedure that is carried out to fit parameters of our orthotropic thermo-visco-hyperelastic model. Results are presented, discussed and compared to previous measures obtained from apparatus that are more complex. Graphical abstract: Image 1 Highlights: A new vertical and transportable biaxial testing device including thermal regulation is designed and built up. The heating system provides quickly a homogeneous temperature of the specimen. A cruciform specimen shape is optimized reach high level of strain (up to 200%). Identification of a viscohyperelastic model coupled with temperature is performed from equal-biaxial tensile results.